2011
DOI: 10.1123/ijsc.4.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Sports Media Decision Making in France: How They Choose What We Get to See and Read

Abstract: This qualitative exploratory case study redresses the deficit of sports media research in France by undertaking a study of those responsible for the production of sports media content. The central question was, What role do sports media producers play in perpetuating dominant ideologies in sport? Participants were experienced male and female sports content decision makers from major French national television and print media. Data were collected through 9 individual semistructured interviews. The findings high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 34 publications
5
29
0
Order By: Relevance
“…Specifically, when an athlete achieved or exceeded the expectation, she or he received considerably more media attention than an athlete who did not. Although this finding has not previously been associated with expectations in sport, it does support some previous suggestions (e.g., Gee & Leberman, 2011) that top sport performers are likely to receive the most media coverage, whilst contradicting other research which has suggested that winning a gold medal does not mean that an athlete will receive more media attention (Hong & Oh, 2017). Furthermore, this finding contradicts research by Kristiansen and colleagues (2011), who suggested that the media can place an immense amount of attention on perceived failures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, when an athlete achieved or exceeded the expectation, she or he received considerably more media attention than an athlete who did not. Although this finding has not previously been associated with expectations in sport, it does support some previous suggestions (e.g., Gee & Leberman, 2011) that top sport performers are likely to receive the most media coverage, whilst contradicting other research which has suggested that winning a gold medal does not mean that an athlete will receive more media attention (Hong & Oh, 2017). Furthermore, this finding contradicts research by Kristiansen and colleagues (2011), who suggested that the media can place an immense amount of attention on perceived failures.…”
Section: Discussionsupporting
confidence: 88%
“…In sport, this means that journalists choose the athletes, teams, and sporting events on which to focus, as well as the language and narrative style that will be used when referring to them (Dominick, 2009;Scheufele & Tewksbury, 2007;Weaver, McCombs, & Shaw, 2004). The findings of published research (e.g., Claringbould, Knoppers, & Elling, 2004;Gee & Leberman, 2011;Hardin & Shain, 2006) suggest that the sports or athletes in receipt of the most media coverage relate to top sport performers, performers from the home nation, sports which receive high levels of audience interest, and sports with historical popularity. Numerous authors have documented that the more media coverage a topic receives, the greater perceived salience that topic has to the audience (e.g., Entman, 1993;Park, Chung, & Lee, 2012;Ragas & Kiousis, 2010).…”
mentioning
confidence: 99%
“…The historical commercial logic governing the sports pages-that men's sports sells because it is what readers expect (Gee & Leberman, 2011;Hardin, 2005Hardin, , 2010Knoppers & Elling, 2004)-was noted in the interviews in this study. Like Hardin (2005) and Rowe (2007), this research found that these sports media decision makers based their ideas of audience readership on personal beliefs and ingrained assumptions rather than hard evidence or research.…”
Section: Ingrained Assumptions About Readershipmentioning
confidence: 90%
“…Research that has explored the underrepresentation of women's sports in the media has pointed to particular conditions of sports newswork that have relegated the coverage of women's sports, in particular the male-dominated, hegemonic nature of sports newsrooms (Gee & Leberman, 2011;Hardin, 2005;Knoppers & Elling, 2004), ingrained assumptions of readership expectations among the profession (Rowe, 2007), and how these play into the systematic nature of sports news production (Theberge & Cronk, 1986). Sports newswork is based on a ''beat '' or ''round'' model, where reporters are assigned to cover particular sports or teams.…”
mentioning
confidence: 98%
“…Although not all research shows that employing more female journalists would increase coverage of women's sport, this fact should not be linked with the reluctance of female journalists to women's sport but with their fear of being accused of "favouring" sportswomen and the unwillingness of publishers to present women's sport (Hardin & Shain, 2005, Kian, 2007. The research by Gee and Leberman showed that the coverage of women's sport has to meet higher criteria compared to men's sport in order to be approved (Gee & Leberman, 2011). Rare research concerning female sport journalists shows that they are still marginalised at work.…”
Section: Sports Journalism and Audience Demandmentioning
confidence: 99%